Process monitoring of glass reinforced polypropylene laminates using fiber Bragg gratings. (8th February 2016) - Mulle, M.; Wafai, H.; Yudhanto, A.; Lubineau, G.; Yaldiz, R.; Schijve, W.; Verghese, N.
Abstract: Hot-press molding of glass-fiber-reinforced polypropylene (GFPP) laminates was monitored using longitudinally and transversely embedded fiber Bragg gratings (FBGs) at different locations in unidirectional laminates. The optical sensors proved to efficiently characterize some material properties; for example, strain variations could be related physical change of the laminate, revealing key transition points such as the onset of melt or solidification. These results were confirmed through some comparison with traditional techniques such as differential scanning calorimetry. After the GFPP plate was released from the mold, residual strains were estimated. Because cooling rate is an important process parameter in thermoplastics, affecting crystallinity and ultimately residual strain, two different conditions (22 and 3 °C/min) were investigated. In the longitudinal direction, results were nearly identical while in the transverse direction results showed a 20% discrepancy. Coefficients of thermal expansion (CTE) were also identified during a post-process heating procedure using the embedded FBGs and compared to the results of a thermo-mechanical analysis. Again, dissimilarities were observed for the transverse direction. With regards to through the thickness properties, no differences were observed for residual strains or for CTEs.